Psychomotor abilities as predictors of actions of handball goalkeepers during saves - Krawczyk, P.; Bodasinski, S. (Polish Journal of Sport and Tourism, 2022)
Introduction The aim of this study was to determine whether the level of selected psychomotor abilities is a predictor of goalkeepers` actions performed when saving throws made by the attacker in and without contact with the defender depending on the court area from which the throws are made.